IMPLEMENTASI TEORI SUPPORT VECTO R MACHINE UNTUK MEMPREDIKSI HARGA PENJUALAN LAPTOP ASUS - Hong William Fondy; Mohammad Fajar; Izmy Alwiah Musdar (KHARISMA Tech, 2019)
This study aims to utilize the support vector regression (SVR) method as a machine learning technique to predict the selling price of laptops and their level of accuracy. Data collection is done through literature, internet and evaluation with MAPE. In this study the authors made the Laptop Price Prediction application using Pycharm with the Python programming language. The test results show that the calculation of the analysis performed by the application produces the same optimization value as the calculation done manually by the MAPE formula, which is 98%. This research was conducted on several online laptop sales webs, such as Tokopedia and Bukalapak. Laptop sales data are collected from online sales webs, used as a basis for experiments. Evaluation The results show that from testing 8 test data the best percentage of accuracy was obtained using MAPE, which is 74%.